2012
DOI: 10.1080/13854046.2012.740077
|View full text |Cite
|
Sign up to set email alerts
|

Risky decision-making in HIV-associated neurocognitive disorders (HAND)

Abstract: Individuals infected with HIV show moderate deficits in decision-making, but the ecological relevance of such deficits on everyday functioning has not previously been described. This study sought to examine the magnitude, cognitive correlates, and everyday functioning impact of risky decision-making impairment in HIV-associated neurocognitive disorders (HAND). Participants included 68 HIV+ individuals with HAND, 78 HIV+ individuals without HAND, and 51 HIV- comparison participants, who were administered the Io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
54
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 59 publications
3
54
0
2
Order By: Relevance
“…These associations between HAND and health-related decision-making were not better explained by other demographic or clinical factors. The decision-making difficulties observed in this study are consistent with the prior literature that has demonstrated poor ability to make advantageous decisions in the context of uncertain rewards and punishments in HIV and HAND (Hardy et al, 2006; Iudicello et al, 2013; Martin et al, 2004; Martin et al, 2013), as well as other clinical populations with known frontostriatal systems dysfunction (e.g., Parkinson’s disease; Perretta, Pari, & Beninger, 2005). The effect sizes that accompanied the significant associations between HAND and health-related decision-making were moderate-to-large, thereby suggesting that such difficulties are of clinical relevance.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These associations between HAND and health-related decision-making were not better explained by other demographic or clinical factors. The decision-making difficulties observed in this study are consistent with the prior literature that has demonstrated poor ability to make advantageous decisions in the context of uncertain rewards and punishments in HIV and HAND (Hardy et al, 2006; Iudicello et al, 2013; Martin et al, 2004; Martin et al, 2013), as well as other clinical populations with known frontostriatal systems dysfunction (e.g., Parkinson’s disease; Perretta, Pari, & Beninger, 2005). The effect sizes that accompanied the significant associations between HAND and health-related decision-making were moderate-to-large, thereby suggesting that such difficulties are of clinical relevance.…”
Section: Discussionsupporting
confidence: 88%
“…These previous studies have shown significant associations between poor decision-making ability and deficits within neurocognitive domains of learning and executive functions (e.g., Iudicello et al, 2013). In addition, at the neural level, Connolly and colleagues (2014) showed that poor monetary decision-making ability in HIV was related to frontostriatal circuit dysfunction (i.e., increased activation in the basal ganglia, anterior cingulate, dorsolateral prefrontal cortex, and insula).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…This effect can be detected among HIV+ individuals with and without a history of substance dependence (Hardy, Hinkin, Levine, Castellon, & Lam, 2006; Iudicello et al, 2013; E Martin et al, 2004; Thames et al, 2012). In a recent study of HIV effects on decision making among substance-using men who have sex with men (MSMs) (E Martin et al, 2013) we found that HIV+ SDIs showed significantly impaired performance on the IGT compared to HIV− SDIs, particularly on the early trials when decision making under ambiguity is most prominently engaged; but performed virtually identically to HIV− SDIs on the Cups Task, a measure of decision making under risk that provides explicit information about the likelihood and magnitude of potential wins and losses.…”
Section: Discussionmentioning
confidence: 99%
“…The HIV literature has suggested that impaired decision making may influence both high risk sexual practices and level of adherence with antiretroviral therapy (Gonzalez et al, 2005; Iudicello et al, 2013; Wardle, Gonzalez, Bechara, & Martin-Thormeyer, 2010). Additionally, as individuals live longer with HIV/AIDS the capacity to participate effectively in health care decisions and live independently will be critically dependent on the integrity of decision making processes.…”
Section: Discussionmentioning
confidence: 99%